A novel multiple access diamond channel model. (22nd September 2020) - Al‐qudah, Zouhair; Al Bataineh, Mohammad; Musa, Ahmed
Summary: This paper introduces a new multiuser communication model, which we call multiple access diamond channel. In this channel model, many sources transmit their signals to a destination in the case of no direct links between the end terminals. Therefore, we employ two parallel relays to extend transmission to the destination. Further, we specifically characterize two different transmission schemes along with their respective achievable rate regions. Then, we develop an outer bound to the transmission in each scheme. Moreover, we present many numerical examples to mainly compare between the two different transmission schemes and to distinguish the case for which we attain the capacity region. Abstract : This paper introduces a new multiuser communication model, which we call multiple access diamond channel. In this channel model, many sources transmit their signals to a destination in the case of no direct links between the end terminals. Therefore, we employ two parallel relays to extend transmission to the destination. Further, we specifically characterize two different transmission schemes along with their respective achievable rate regions. Then, we develop an outer bound to the transmission in each scheme.